Carbon Stock Stratification of Peat Soils in South Kalimantan, Indonesia - Siti Zakiah; Muhammad Noor; Dedi Nursyamsi (Center for Journal Management and Publication, 2014)
Carbon stock in peat soils is very high, it is necessary to prudent in its management because peat soils is emitting greenhouse gases such as CO2 during land clearing due to oxidation of peat layer. This research was conducted to study soil carbon stock stratification in relation to soil physical and chemical properties. The carbon stock stratification was based on maturity degrees of peat. The study was conducted in Pulau Damar Village, Hulu Sungai Utara District, South Kalimantan Province on land use rubber. The location of the study area was determined by using the purposive sampling method. All data obtained were analyzed by Excel spreadsheets and drawn on a CorelDraw 12. The results showed that the amount of carbon stock was influenced by the maturity degrees of peats, peat sapric degres has higher carbon stock than of hemik and fibric with a ratio of 2.0: 1.5: 1. The relationship between soil carbon stock with soil physic (Bulk Density, BD) and chemical properties (pH, Eh, Fe, and total-N) were not significantly.